Market Structure and College Access in the US - Emily E. Cook (CESifo GmbH, 2025)
State governments provide grants to students to subsidize college attendance. In response, colleges can adjust their tuition, aid policies, and admission standards, affecting equilibrium enrollment and pass-through of aid to students. To quantify demand- and supply-side responses, I develop a model that incorporates the geographic nature of the market and strategic competition between individual colleges. Simulations demonstrate that college responses are meaningful: when students receive 1,000 to attend in-state public colleges, these colleges absorb over 40% of the subsidy on average and raise admissions standards, reducing the enrollment effect of the policy. Close competitors see enrollment declines of 2-3%.
Keywords: I23; I28; L13; L31; 330; college choice; college admission; college enrollment; financial aid; mixed oligopoly; non-profit firms; demand estimation